Perceptions of environmental changes and Lethargic crab disease among crab harvesters in a Brazilian coastal community - Firmo Angélica MS; Tognella Mônica MP; Có Walter LO; Barboza Raynner RD; Alves Rômulo RN (BMC, 2011)
Abstract Background Lethargic Crab Disease (LCD) has caused significant mortalities in the population of Ucides cordatus crabs in the Mucuri estuary in Bahia State, Brazil, and has brought social and economic problems to many crab-harvesting communities that depend on this natural resource. The present work examined the perceptions of members of a Brazilian crab harvesting community concerning environmental changes and the Lethargic Crab Disease. Methods Field work was undertaken during the period between January and April/2009, with weekly or biweekly field excursions during which open and semi-structured interviews were held with local residents in the municipality of Mucuri, Bahia State, Brazil. A total of 23 individuals were interviewed, all of whom had at least 20 years of crab-collecting experience in the study region. Key-informants (more experienced crab harvesters) were selected among the interviewees using the "native specialist" criterion. Results According to the collectors, LCD reached the Mucuri mangroves between 2004 and 2005, decimating almost all crab population in the area, and in 2007, 2008 and 2009 high mortalities of U. cordatus were again observed as a result of recurrences of this disease in the region. In addition to LCD, crabs were also suffering great stock reductions due to habitat degradation caused by deforestation, landfills, sewage effluents, domestic and industrial wastes and the introduction of exotic fish in the Mucuri River estuary. The harvesting community was found to have significant ecological knowledge about the functioning of mangrove swamp ecology, the biology of crabs, and the mass mortality that directly affected the economy of this community, and this information was largely in accordance with scientific knowledge. Conclusions The study of traditional knowledge makes it possible to better understand human interactions with the environment and aids in the elaboration of appropriate strategies for natural resource conservation.